A study on the effect of blue light on kidney stone formation in rats via the brain-kidney axis - Dao-Cheng Fang; Yuan-Yuan Hu; Chao Wang; Jie Fan; Hui Wen (Scientific Reports)
Abstract Kidney stones, a common urological disease, may involve the brain-kidney axis in their formation, though the specific mechanism remains unclear. This study aimed to investigate the effects of blue light on relevant metabolic indicators and oxidative stress status in rats with kidney stones through the brain-kidney axis. A rat model of kidney stones was established by administering 1% ethylene glycol and 2% ammonium chloride. Subsequently, blue light intervention was applied, and the outcomes were compared with those of a control group of normal rats. Our findings revealed that rats with kidney stones receiving blue light intervention exhibited significantly increased levels of antidiuretic hormone, intensified oxidative stress response, and augmented stone formation compared to kidney stone rats without blue light intervention. However, in normal rats, blue light intervention did not cause significant changes in these indicators. In summary, this study indicates that under pathological conditions, blue light may promote the secretion of antidiuretic hormone in serum and enhance oxidative stress response in renal tissues by affecting the brain-kidney axis, thereby accelerating the formation of kidney stones in rats.